AN EXPLORATION OF THE IMPACT OF POSITIVE EMOTIONS AND HAPPINESS ON MENTAL HEALTH USING THE CONCEPT OF PSYCHOLOGICAL CAPITAL - Elfitra Azliyanti; Purbo Jadmiko; Reni Yuliviona; Titin Sugiarti (Jurnal Apresiasi Ekonomi, 2025)
The study aim to examine the correlation between positive emotions and happiness in the context of mental health, with psychological capital serving as a mediating factor. The subject of this study is a student enrolled at Universitas  Bung Hatta Padang. Within the realm of student life, positive emotions and happiness are frequently recognized as significant elements that impact their psychological capital. Nevertheless, there is limited research that has investigated the mechanisms underlying this link, namely the mediating role of psychological capital. This study employs a quantitative research design utilizing a survey methodology, which includes a diverse group of students from different faculties at Universitas Bung Hatta Padang. Information is gathered by using a modified questionnaire based on previously approved tools. Research hypotheses are tested by employing multiple regression analysis techniques. The findings indicate that experiencing positive emotions and happiness has a beneficial impact on the mental health of students. Furthermore, research has demonstrated that psychological capital plays a crucial intermediary role in the connection between positive emotions, happiness, and mental health. The practical ramifications of this research indicate that colleges should establish a campus atmosphere that fosters positive emotions, and allocate resources towards initiatives that seek to enhance psychological capital.Keywords : positive emotions; psychological capital; happiness; mental health